Proceedings of the Joint Meeting of the Twenty-Third EACSL Annual Conference on Computer Science Logic (CSL) and the Twenty-Nin 2014
DOI: 10.1145/2603088.2603117
|View full text |Cite
|
Sign up to set email alerts
|

Logics with counting and equivalence

Abstract: We consider the two-variable fragment of first-order logic with counting, subject to the stipulation that a single distinguished binary predicate be interpreted as an equivalence. We show that the satisfiability and finite satisfiability problems for this logic are both NEXPTIME-complete. We further show that the corresponding problems for two-variable first-order logic with counting and two equivalences are both undecidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In [4] it is shown that finite satisfiability for C 2 interpreted over structures where two binary relations are interpreted as forests of finite trees (which subsumes the case of two successor relations on two linear orders) is NExpTime-complete. [30] shows that the satisfiability and finite satisfiability problems for C 2 with one equivalence relation are both NExpTime-complete. All extensions of C 2 mentioned above allow arbitrary number of other binary relations.…”
Section: Introductionmentioning
confidence: 99%
“…In [4] it is shown that finite satisfiability for C 2 interpreted over structures where two binary relations are interpreted as forests of finite trees (which subsumes the case of two successor relations on two linear orders) is NExpTime-complete. [30] shows that the satisfiability and finite satisfiability problems for C 2 with one equivalence relation are both NExpTime-complete. All extensions of C 2 mentioned above allow arbitrary number of other binary relations.…”
Section: Introductionmentioning
confidence: 99%
“…Our work also gives rise to other questions. We suspect that our results can be extended to ω-languages, and we would like to adapt them to C 2 , which extends FO 2 with counting quantifiers [26,31]. We also plan to explore further the computational power of our automata model, for instance, to establish a pumping lemma that allows us to prove that some context-free languages are not PI languages.…”
Section: Discussionmentioning
confidence: 99%
“…Finite satisfiability of C 2 with two forests was shown in [10] to be NEXPTIME-complete. Satisfiability and finite satisfiability of C 2 with a single equivalence relation was shown to be NEXPTIME-complete, while C 2 with two equivalence relations is undecidable [26]. Decidability of extensions of F O 2 with successor relations, order relations, and equivalence relations without counting were studied [13], [16], [17], [20], [21], [30].…”
Section: The Two-variable Fragment and Alcqiomentioning
confidence: 99%